Relationship Among the Tendency to Cyber-Aggression, Aggressiveness, and Empathy in Adolescence - Светлана С. Антипина; Анастасия В. Микляева (Rossijskij psihologičeskij žurnal., 2021)
Introduction. This study aims to examine the relationship among the tendency to various forms of cyber-aggression, aggressiveness, and empathy in adolescence. Cyber-aggression is understood as the deliberate infliction of harm on other Internet users. The forms of cyber-aggression are distinguished on the basis of a typological model of cyber-aggression proposed by K. Runions, which was first used to analyze the online behavior of Russian adolescents. Methods. The study involved 196 adolescents aged between 12 and 15 years. Empirical data were collected using the Cyber-Aggression Typology Questionnaire modified for Russian-speaking respondents, the Buss–Perry Aggression Questionnaire modified by S. N. Enikolopov, and the Balanced Emotional Empathy Scale by Mehrabian (modified by N. Epstein). Results. There was no relationship among the tendency to cyber-aggression, aggressiveness, and empathy, which would be universal throughout the entire adolescence. The tendency to cyber-aggression significantly correlates with aggressiveness after 14 years of age and with empathy after 15 years of age. Aggressiveness is not a significant predictor of adolescent cyber-aggression; empathy determines the tendency to cyber-aggression (with a negative sign) only among 15-year-old adolescents. Discussion. We assumed that cyber-aggression has different psychological meanings at various stages of adolescence – cyber-aggression as a form of ‘social tests’ in early adolescence, which is not related to personality traits of an individual, and cyber-aggression as a manifestation of stable personality traits (primarily, lack of empathy) in late adolescence. Conclusion. We can draw a conclusion that there is a need for a differentiated approach to prevention and correction of adolescent cyber-aggression that takes into account its psychological meanings at various stages of adolescence.